Jebakan Algoritma dalam Dunia Pendidikan di Indonesia; Bagaimana Cara Melampauinya? - Mbukut, Antonius (Sekolah Tinggi Katolik Santo Yakobus Merauke, 2025)
This article aims to describe the process of artificial intelligence technology trapping students in misleading information and describe the urgency of developing critical thinking skills in educational institutions in Indonesia. This research uses a qualitative descriptive method. Data sources were obtained by conducting a literature review. The researcher analyzed the process of artificial intelligence technology trapping students in misleading information based on theories and ideas found in the literature review. Based on the results of the research, it was found that artificial intelligence technology traps students in misleading information through the algorithms of various social media platforms, search engines and educational applications that they use. The algorithms use data scraping and analysis methods to collect the most relevant and most interesting information for students. Without realizing it, students end up trapped in a bubble of information according to their preferences and polarized according to their own beliefs. It becomes difficult for them to learn and accept different views. This can be prevented by developing critical thinking skills in schools. Schools should provide an environment conducive to students being able to assess and evaluate all the information they receive from artificial intelligence technologies. This ability is referred to as critical thinking skills.